FUNCTIONAL STRENGTH TRAINING FOR PHYSICAL EDUCATION - VanKouwenberg, Nate, 1981- (Human Kinetics, 2025)
"This applied professional reference provides physical education teachers with the knowledge, tools, and skills required to introduce functional strength training to children and adolescents. This book focuses exclusively on functional strength training, which is vital to student-athletes, but equally valuable to students who don't play a sport"--